HR METRICS- ITS IMPACT ON RETURN ON INVESTMENT : A STUDY ON SELECT ORGANIZATIONS IN ASSAM. - Kalita, Dr. Kabita; Das, Ananya (The journal of contemporary issues in business and government, 2022)
Recent developments in the field of Human Resource Management has led to the evolution of Human Resource (HR) metrics and Workforce analytics. Without the use of HR metrics, it is observed that organizations measure the effectiveness of HR policies by a trial and error method. Prior to the introduction of metrics, the result of the HR policies and efforts of people involved went unnoticed. But with the introduction of HR Metrics, a new revolution has come into being. Objective: The present study is thus an attempt to see the impact of metrics on one of the most essential element of organization i.e the Return on investment (ROI). Methodology: Each organization wants to have a positive ROI. The study was conducted across several organizations in Assam. HR professionals were involved and a questionnaire was given based on the Likert scale. Answers were collected and those were further studied with various statistical tools like Reliability analysis, ANNOVA, Correlation, Regression. Findings: There is a positive relationship between HR metrics and Return on investment (Trivedi, 2015). The present study is also aligned and in consistency with the previous studies and finds a significant relationship between HR Metrics and Return on investment. The study was done taking into account three variables of research and all of them had an impact on Return on investment. Novelty: This research takes into account three new dimensions of HR metrics while undertaking the study which were not done previously.